Mechanism and structure studies of cinnamaldehyde/cyclodextrins inclusions by computer simulation and NMR technology. (15th August 2018) - Sun, Qiaomei; Tang, Peixiao; Zhao, Ludan; Pu, Hongyu; Zhai, Yuanming; Li, Hui
Highlights: Inclusion mechanisms and structures of CNMA-CDs were investigated. Docking and molecule dynamics predicted detailed inclusion information. The inclusion abilities followed the order: DM > HP > β-CD. The benzene ring of CNMA inserted into hydrophobic cavity of CDs. The solubility and dissolution rate of CNMA were improved after inclusion. Abstract: This work aims to explore the inclusion mechanism and structure of cinnamaldehyde (CNMA) and cyclodextrins (CDs), and to provide some theoretical information for the application of CNMA and its inclusion. In this study, we prepared three kinds of inclusion and investigated the mechanism and structure by theory and experiment. Molecular docking and dynamical simulations presented a stable 1:1 inclusion complex and the visual structure model. The structural features indicated that the benzene ring of CNMA was enclosed in the hydrophobic cavity of CDs, which were consistent with the results of 1 H NMR, 2D-ROESY, Fourier transform infrared spectroscopy. The inclusion mechanism studies showed that the inclusion process was driven mainly by enthalpy with the binding constant following the order of DM (dimethyl) > HP (hydroxypropyl) > β-CD. Moreover, the inclusion complex showed an advantageous water solubility and dissolution rate compared with CNMA.